Evaluating Hydrocarbon Prospects and Petrophysical Properties in Sepinggan Formation, East Kalimantan's Lower Kutai Basin - Purnomo, Rezandy Purnomo Setyo; Rohmana, Rian Cahya; Atmoko, Widi (Journal of Earth Energy Science, Engineering, and Technology, 2023)
This study aims to determine hydrocarbon zones and analyze petrophysics in the Sepinggan Formation, located in the lower Kutai Basin, which is one of the oil and gas producing formations in Indonesia. The data used includes 5 well log data and mudlog data. The results of the study show that the Sepinggan Formation has 14 potential zones dominated by carbonate sandstone lithology with a slight mixture of coal. Some key findings in the petrophysical analysis include the largest average shale volume of about 41% in zone 1 of well SPG-V8, the largest average porosity of about 24% in zones 1 and 2 of well SPG-V1, the largest average permeability of about 2591.08 mD in zone 1 of well SPG-V2, and the largest average water saturation of about 56% in zone 2 of well SPG-V7. Based on these results, further evaluation of hydrocarbon potential in the identified potential zones and optimization of exploration and exploitation techniques are needed to improve the efficiency of oil and gas production in the Sepinggan Formation.